PENGARUH INVENTORY INTENSITY, DEFERRED TAX EXPENSE DAN ADVERTISING INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2017-2023) - Yanti, Erdini; Utami , Citra Kharisma; Maulany , Siti Ganiah (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The aim of this research is to determine the effect of Inventory Intensity, Deferred Tax Expense, and Advertising Intensity on tax aggressiveness in pharmaceutical companies on the IDX in 2017-2023. This research uses quantitative methods. The population in this study was 9 companies. In this research, sampling used the purposive sampling method. The independent variables in this research are, Inventory Intensity, Deferred Tax Expense, Advertising Intensity and the dependent variable is tax aggressivenes. The data analysis technique used is multiple linear regression analysis. The results of the research analysis show that Inventory Intensity has no effect on tax aggressiveness. This is proven by the significance result of 0.596 which is greater than 0.05 while Deferred Tax Expense has an effect on tax aggressiveness. These results are proven by the significance result of 0.013 which is smaller than 0.05 and Advertising Intensity has no effect on tax aggressiveness. These results are proven by the significance result of 0.426 which is greater than 0.05. The coefficient of determination or R2 value of Inventory Intensity (INV), Deferred Tax Expense (DTE), Advertising Intensity (ADV) on Tax Aggressiveness is 16%.